2020
DOI: 10.3390/nano10050882
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiO2/WO3 Composite Nanofibers by a Water-Based Electrospinning Process and Their Application in Photocatalysis

Abstract: TiO2/WO3 nanofibers were prepared in a one-step process by electrospinning. Titanium(IV) bis(ammonium lactato)dihydroxide (TiBALDH) and ammonium metatungstate (AMT) were used as water-soluble Ti and W precursors, respectively. Polyvinylpyrrolidone (PVP) and varying ratios of TiBALDH and AMT were dissolved in a mixture of H2O, EtOH and CH3COOH. The as-spun fibers were then heated in air at 1 °C min−1 until 600 °C to form TiO2/WO3 composite nanofibers. Fiber characterization was done using TG/DTA, SEM–EDX, FTIR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…However, the TiO 2 with a wide band gap was only excited by ultraviolet light contributing only 6% of the solar spectrum; moreover, the photogenerated charge carriers in the TiO 2 easily recombine, which adversely affects the practical photoactivated performance of the TiO 2 . Recently, one-dimensional TiO 2 oxide coupled with other narrow wide band gap materials with a suitable band alignment was revealed as a promising approach to improve the intrinsic photoactivity of the TiO 2 [3,7]. In particular, construction of oxide heterostructures with a type II band alignment is advantageous to suppress the recombination of photogenerated electron-hole pairs and improve the photocatalytic efficiency because of formation of an inner electric field at the heterointerface [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the TiO 2 with a wide band gap was only excited by ultraviolet light contributing only 6% of the solar spectrum; moreover, the photogenerated charge carriers in the TiO 2 easily recombine, which adversely affects the practical photoactivated performance of the TiO 2 . Recently, one-dimensional TiO 2 oxide coupled with other narrow wide band gap materials with a suitable band alignment was revealed as a promising approach to improve the intrinsic photoactivity of the TiO 2 [3,7]. In particular, construction of oxide heterostructures with a type II band alignment is advantageous to suppress the recombination of photogenerated electron-hole pairs and improve the photocatalytic efficiency because of formation of an inner electric field at the heterointerface [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we used electrospinning and precursors soluble in water to prepare TiO 2 /WO 3 composite nanofibers and demonstrated that conditions of heat treatment influenced the nanofibers’ final composition [ 29 ]. When the fibers are annealed in inert conditions, the polymer decomposes without undergoing combustion.…”
Section: Introductionmentioning
confidence: 99%
“…It was chosen as the fiber material in this study due to its advantageous mechanical properties, excellent fiber-forming ability, biodegradability, stability in water, and cost-effectiveness [ 13 , 15 ]. Electrospinning has become a popular method for the synthesis of micro- and nanofibrous materials due to the use of relatively simple manufacturing equipment, low spinning cost, variety of spinnable materials, and highly controllable processes [ 16 , 17 ]. Moreover, micro- to nanoscale fibers display a high surface-area-to-volume ratio, good flexibility, high porosity, and superior stiffness and tensile strength than when compared to other forms of the spun material [ 15 ].…”
Section: Introductionmentioning
confidence: 99%